The presence of anticardiolipin antibodies in adults may be influenced by infections in infancy. - Edwards, C; Syddall, H; Jameson, K; Williams, E; Polosa, R; Goswami, R; Dennison, E; Arden, N; Cooper, C (2008)
OBJECTIVES: There has been limited success defining environmental factors important in the development of antiphospholipid (Hughes) syndrome (APS). Recent work suggests that the perinatal environment may be important in the development of other autoimmune diseases. We measured anticardiolipin antibodies (aCL) in a general population with well-defined early lives to see whether fetal and infant growth and infections were associated with aCL positivity in adult life. METHODS: aCLs were measured using an ELISA in 1384 individuals from the Hertfordshire cohort study. We investigated associations between the presence of aCL and early growth and infectious exposure in infancy in men and women. RESULTS: ELISA positive aCL (IgM and IgG) was present in 22 (3%) men and 15 (2%) women. Using the highest octile of aCL results, in men higher birth weight (per lb of birth weight: OR 1.18, 95% CI 1.02-1.36, P = 0.02) and diarrhoeal infection in the first year of life (OR 2.55, 95% CI 1.10, 5.92, P = 0.03) were associated with an increased likelihood of being aCL positive. In women, diarrhoeal infection in the first year of life was also associated with an increased likelihood of aCL positivity (OR 2.23, 95% CI 1.01, 4.91, P = 0.05). For IgG titre in men, significant relationships were found with sharing a bedroom (regression coefficient 1.13; 95% CI 1.05, 1.22; P = 0.02) and diarrhoea in the first year (coefficient 1.25; 95% CI 1.00, 1.56; P = 0.05). CONCLUSION: A developing immune system when exposed to the infectious environment may influence the likelihood of producing aCL in adult life.